The effect of enteral nutrition on adipokines in patients with acute pancreatitis - Sarah J. L. McKenzie; Rakesh Premkumar; Kathryn J. Askelund; Sayali A. Pendharkar; Anthony R. J. Phillips; John A. Windsor; Maxim S. Petrov (Journal of Nutritional Science, 2015)
The mechanism behind the beneficial effects of enteral nutrition (EN) for patients with acute pancreatitis (AP) is largely unknown. Adipokines, as mediators of metabolism and inflammation, may be a possible mechanism. The study aimed to investigate the effect of EN on adipokines early in the course of AP. Patients with AP were randomised to EN or nil-by-mouth (NBM). Blood samples were taken on the first 4 d of admission and adipokine concentrations for adiponectin, leptin, omentin, resistin and visfatin were determined by ELISA assays. A linear mixed model analysis was run to determine differences in adipokine concentrations between the two study groups. A total of thirty-two patients were included in the study. Omentin concentrations were significantly higher in patients who received EN compared with NBM across the first 4 d of admission (mean difference: 11·6 (95 % CI 1·0, 22·3) ng/ml; P = 0·033). Leptin concentrations were significantly higher in patients who received EN compared with NBM after adjusting for age, sex and BMI (mean difference: 2·3 (95 % CI 0·1, 4·5) ng/ml; P = 0·037). No significant difference in adiponectin, resistin or visfatin concentrations were observed between the two study groups. EN significantly increases omentin and leptin concentrations in AP. Future research should be directed towards understanding whether these adipokines are responsible for the therapeutic benefits of EN.